The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/jso.26909
|View full text |Cite
|
Sign up to set email alerts
|

Esophagojejunostomy after total gastrectomy: A systematic review and meta‐analysis comparing hand‐sewn and stapled anastomosis

Abstract: This review aims to evaluate the surgical outcomes of hand‐sewn esophageal anastomosis compared to mechanical anastomosis to reconstruct total gastrectomy. A systematic review and meta‐analysis of comparative studies evaluating hand‐sewn and stapled anastomosis were performed. A total of 12 studies were selected, comprising 1761 individuals. The results indicate that the hand‐sewn and stapled esophageal anastomosis have similar surgical outcomes. Stapled anastomosis has a shorter operation time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Overall complications rate in our study was 18.1%, with no significant difference between the analyzed groups (21% for hand-sewn; 16% for stapler group; P=0.50), same as reported in a recent meta-analysis [6]. The work of Watanabe, et al from Japan on over 20 000 patients reported overall morbidity at 26.2%, which is similar to our study [37].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Overall complications rate in our study was 18.1%, with no significant difference between the analyzed groups (21% for hand-sewn; 16% for stapler group; P=0.50), same as reported in a recent meta-analysis [6]. The work of Watanabe, et al from Japan on over 20 000 patients reported overall morbidity at 26.2%, which is similar to our study [37].…”
Section: Discussionsupporting
confidence: 90%
“…There was no significant difference in hospital mortality between the hand-sewn and stapled anastomosis groups in our study (P=0.837). A meta-analysis on esophagogastric anastomosis by Markar et al, as well as recent meta-analysis on esophago-jejunal anastomosis, confirmed these results [6,50]. Two large-cohort studies performed using the National Cancer Databases reported in-hospital mortality (2.2%), 30-day mortality (0.9-4.7%), and 90-day mortality (9.1%) [37,51].…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations